KEAMANAN INFORMASI (INFORMATION SECURITY) PADA APLIKASI SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA - Enggar Novianto; Erik Herman Heri Ujianto; Rianto Rianto (LPPM Universitas Abdurrab, 2023)
The development of information technology in the current era is growing rapidly, which is indicated by the emergence of many innovative programs in personal information services. One of the contenders for such information is SIMPEG, an application from Sebelas Maret University. The purpose of this study is to determine the application of information security to address the aspects of confidentiality, integrity and availability of information. This application ensures the security of user's personal information and employee data. The results of this study are that employees are required to register an account using an email that has been registered with SSO. Users of this application are lecturers and education staff including general users and SIMPEG operators. The SIMPEG application also guarantees the confidentiality of each employee's personal data and can only be seen by Sebelas Maret University internal employees. The purpose of registering an account through NIP/NIK and employee staff email is with the aim of preventing actions that can harm the institution. One of the rules for using this application is that it is forbidden to update, copy and delete data unless the SIMPEG operator is responsible for updating the data.